2016
DOI: 10.1384/jsa.23.73
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Peak Detection Algorithms for XPS Spectra

Abstract: In order to evaluate three peak detection algorithms, the influences of parameter values used were examined using digitized synthetic XPS spectra with different levels of noise. The three peak detection algorithms are the Threshold Curve of the Second Derivative (2nd DER method), the Directly Calculating Peak and Background Relations at a Candidate Peak (PB method), and the Rough Estimation of Spectrum Background (BGD method). The peak detection results clearly showed that particular combination of parameter v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In this context, we define the achievable detection limit as the smallest atomic concentration that can be considered statistically different from zero when a specific background‐subtraction method is applied to a measured spectrum (e.g., automated measurements of atomic concentration). This quantity may differ from the ultimate detection limit of an acquired spectrum corresponding to the smallest atomic concentration capable of producing a peak that is detectable above the background by eye or by a peak‐detection algorithm . Derivation of the RBSV for such peak‐detection methods is beyond the scope of this work.…”
Section: Optimal Measurement Strategies For Small Peaksmentioning
confidence: 99%
“…In this context, we define the achievable detection limit as the smallest atomic concentration that can be considered statistically different from zero when a specific background‐subtraction method is applied to a measured spectrum (e.g., automated measurements of atomic concentration). This quantity may differ from the ultimate detection limit of an acquired spectrum corresponding to the smallest atomic concentration capable of producing a peak that is detectable above the background by eye or by a peak‐detection algorithm . Derivation of the RBSV for such peak‐detection methods is beyond the scope of this work.…”
Section: Optimal Measurement Strategies For Small Peaksmentioning
confidence: 99%
“…As a preliminary experiment, we tried two implementable methods for peak identification: the threshold curve of the second derivative method (2nd DER method) and the directly calculating peak and background relations at a candidate peak method (PB method) (Furukawa et al, 2016). As a consequence, we found that it is difficult to distinguish between broad peaks and large noise in the 2nd DER method, and the PB method hardly identifies peaks with narrow widths and low intensities from noise.…”
Section: Algorithm Of Peak Identificationmentioning
confidence: 99%
“…We applied the methods described in Section 4.2 to actual data and plotted intensity and SNR according to kinetic energy and sweeps, respectively. We used a window width of 11 and a polynomial degree of 4 for the parameters of the filter, referring to the work of Furukawa et al (2016). The results are shown in Fig.…”
Section: Quantitative Evaluation Of the Formulation Of The Snrmentioning
confidence: 99%
See 1 more Smart Citation